2008
DOI: 10.1089/jwh.2007.0468
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Coronary Heart Disease and Health-Related Quality of Life: Findings from 10 States from the 2004 Behavioral Risk Factor Surveillance System

Abstract: People with CHD have significantly impaired HRQOL compared with those without CHD. HRQOL among women with CHD is worse than that among men with CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 71 publications
2
35
1
2
Order By: Relevance
“…[90][91][92][93][94][95][96][97][98] These differences can be found within 1 month after an acute MI, as well as over the longer term. [92][93][94] Women treated with CABG surgery, despite recovering similarly to men, also have impaired health status compared with men at both 6 and 12 months postoperatively.…”
Section: Health Status and Sexmentioning
confidence: 95%
“…[90][91][92][93][94][95][96][97][98] These differences can be found within 1 month after an acute MI, as well as over the longer term. [92][93][94] Women treated with CABG surgery, despite recovering similarly to men, also have impaired health status compared with men at both 6 and 12 months postoperatively.…”
Section: Health Status and Sexmentioning
confidence: 95%
“…78,116,117 They have been used to assess population group differences and have shown expected differences among persons with and without cardiovascular risk factors 88,89,92,93,102 and conditions. [77][78][79]85 Studies have assessed how the Healthy Days measures compare to other HRQOL measures and could be calibrated to other scales. 118,119 The Healthy Days measures appear to be valid for adolescents, although further studies may be needed.…”
Section: Lloyd-jones Et Al Setting National Goals For Cardiovascular mentioning
confidence: 99%
“…Although the terms QOL and HRQOL are often used interchangeably, previous research has found that the QOL of women with coronary heart disease (CHD) is poorer than that in men. [8][9][10][11] College of Nursing, University of South Florida, Tampa, Florida. 10.1089=jwh.2010.1937 Beckie and Hayduk 2 evaluated the global QOL and perceptions of health of 46 women and 260 men 12 weeks after coronary artery bypass graft (CABG) surgery.…”
mentioning
confidence: 99%